T-Shirts That Tell Tales: Remembrance and Resistance in T-Shirt Designs in Hawaii - Kelly, Marjorie (2012)
The imagery on T-shirts produced in Hawai‟i for the resident population are carefully thought out reflections of and responses to local concerns. They express the wearer‟s self-image and group identity, as well as his/her social values and allegiance. The article examines the T-shirt images designed for two specific groups: locals (or non-Caucasian, lifelong residents of the islands) and Native Hawaiians. Given the relentless pace of globalization in the 1990s, island residents felt their way of life was threatened and responded by remembering the past and/or wearing T-shirts that alluded to another way of life. Whether the images recall the communal society of plantation life or the political and spiritual aspects of Hawaiian identity, the widelyworn shirts described in the article provide insight into island society during a time of intense change.